2022
DOI: 10.1039/d2fo02758e
|View full text |Cite
|
Sign up to set email alerts
|

Component analysis and anti-pulmonary fibrosis effects of Rosa sterilis juice

Abstract: Rosa sterilis is a new variety of Rosa roxburghii Tratt, and is rich in bioactive substances, but its role in pulmonary fibrosis has not been elucidated. The purpose of this...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…38 Surprisingly, WRS also inhibited the mRNA expression of inflammatory mediators, especially on IL-6 and COX-2 ( p < 0.01). This may be attributed to the high content of vitamin C and SOD in R. sterilis fruits, 11 both of which can help reduce the production of inflammatory mediators by reducing oxidative stress and neutralizing free radicals. 39…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…38 Surprisingly, WRS also inhibited the mRNA expression of inflammatory mediators, especially on IL-6 and COX-2 ( p < 0.01). This may be attributed to the high content of vitamin C and SOD in R. sterilis fruits, 11 both of which can help reduce the production of inflammatory mediators by reducing oxidative stress and neutralizing free radicals. 39…”
Section: Resultsmentioning
confidence: 99%
“…14 Nevertheless, the biological function of RS has not been fully studied. Wang et al found that RS juice could inhibit TGF-β1-induced epithelial–mesenchymal transition and fibroblast differentiation; 11 Zhu et al demonstrated that R. sterilis flavonoids showed strong α-glucosidase inhibitory activity in vitro . 15…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This fruit has traditionally been used as a food and herbal medicine for certain diseases such as diarrhea, hyperlipidemia, and enteritis . Current research indicates that Rosa roxburghii juice has antipulmonary fibrosis effects . In addition, the Rosa roxburghii fruit has been found to have antioxidant, antidiabetic, antimutagenic, antiatherosclerotic, antitumor, and radiation protection activities. , By 2020, the Rosa roxburghii planting area in Guizhou Province expanded to 133,300 ha, and the output of Rosa roxburghii fruits and related products reached 100 tons and 26,200 tons, respectively.…”
Section: Introductionmentioning
confidence: 99%